Perancangan Interior Education Centre di Surabaya - Cynthia Kartono; Hedy Constancia Indrani (Intra, 2014)
Education is a part that can not be discharged in the life of every person. There are a variety of ways to education, for example, an alternative course that is in great demand. Various agencies in Surabaya developing courses with a variety of facilities and quality of learning programs. The children became the object of major markets in the need for education. Realizing a container that is able to maximize the facilities and a good learning program in Surabaya for children aged 6-18 years as a reference design. Not all colleges realize the importance and influence of interior design in the learning process for children. Therefore, the concept of interior design Education Centre is taking the concept grow as problem solving where each design is focused for growing children independently, with a focused spatial planning, the design of a free and independent area for the children to learn, as well as the processing of each element of the interior by using color that is able to provide peace and activeness in learning. Good medium expected to produce children with intelligence and good personal.